2012
DOI: 10.1002/apj.486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooling rate on the partition of heavy and alkali metals during waste incineration

Abstract: The cooling rate is the most important factor affecting the partition of vapor metallic compounds in the downstream of waste incinerator. In this work, an experiment was performed in a bench-scale incinerator to reveal the relationship between the cooling rate and the partition of heavy and alkali metals. Experimental results showed that the increase in cooling rate had a negative effect on the capture of heavy and alkali metals by silica filter in the temperature range of 26-160 • C/s. The higher cooling rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…This special theme can be divided into four research groups, which are described as follows: The first group of papers covers a wide spectrum of coal science and technology, including the gasification reactivity of coal‐char, characterization of coal surface functional group, NOx emission control from coal‐fired power stations by methane reburn, ignition characteristics of coal during oxy‐fuel combustion, and techno‐economic analysis of coal‐fired power plant with post‐combustion CO 2 capture equipments. The second group provides insights into key issues associated with biomass utilization, such as combustion mechanisms of biomass, development of biosorbents for waste water treatment, biodiesel production and the emission of heavy metals during waste incineration. The third group focuses on the solid mixing mechanisms in a bubbling fluidized bed reactor. The fourth group investigates the characterization of activated carbon fiber modified by plasma.…”
Section: An Overview Of Papers In This Special Themementioning
confidence: 99%
See 1 more Smart Citation
“…This special theme can be divided into four research groups, which are described as follows: The first group of papers covers a wide spectrum of coal science and technology, including the gasification reactivity of coal‐char, characterization of coal surface functional group, NOx emission control from coal‐fired power stations by methane reburn, ignition characteristics of coal during oxy‐fuel combustion, and techno‐economic analysis of coal‐fired power plant with post‐combustion CO 2 capture equipments. The second group provides insights into key issues associated with biomass utilization, such as combustion mechanisms of biomass, development of biosorbents for waste water treatment, biodiesel production and the emission of heavy metals during waste incineration. The third group focuses on the solid mixing mechanisms in a bubbling fluidized bed reactor. The fourth group investigates the characterization of activated carbon fiber modified by plasma.…”
Section: An Overview Of Papers In This Special Themementioning
confidence: 99%
“…Chemical reaction and aerodynamic studies have shown that flue gas cooling rate has significant effects on fine particulate formation, however, little study has been done on the relationship between the cooling rate and the partition of heavy and alkali metals during waste incineration. Therefore, the objective of paper is to investigate the influences of flue gas cooling rate on the gas–solid transformation of the most toxic heavy metals such as Pb, Cr, Cu, As and Cd. The results show that the increase of cooling rate leads to a decrease in the capture efficiency of heavy metals by silica filter in the range of 26–160 °C/s.…”
Section: Emission Of Heavy Metals During Waste Incinerationmentioning
confidence: 99%